A straightforward guide to the sarcomeric basis of cardiomyopathies. Issue 24 (30th September 2014) - Lopes, Luís R; Elliott, Perry M
Abstract : The sarcomere is the principal contractile unit of striated muscle. Mutations in genes encoding sarcomeric proteins are responsible for a range of diseases including hypertrophic, dilated and restrictive cardiomyopathies and ventricular non-compaction. The downstream molecular pathways leading to these heterogeneous phenotypes include changes in acto-myosin cross-bridge kinetics, altered mechanosensation, disturbed calcium sensitivity, de-regulated signalling pathways, inefficient energetics, myocardial ischaemia and fibrosis. The elucidation of the genetic causes of cardiomyopathy has helped in understanding the structure and function of the sarcomere and a more detailed knowledge of the sarcomere and its associated proteins has suggested additional gene candidates. The new hope is that these advances will stimulate the discovery of disease-modifying drugs.